Kedudukan dan Sistematika Filsafat Ilmu dalam Rasionalisasi Ilmu Pengetahuan - Isno, Mohammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Rationalization Science happened since Rene Descartes with a skeptical attitude-metodisnya doubting everything, except him who is hesitant (cogito ergo sum). This attitude continued in Auf Klarung, an era which is an attempt to reach a rational man about himself and nature. The purpose of this paper is to describe the position and systematic philosophy of science in the rationalization of science. Relates to a process of rationalization of knowledge derived from sensory experience, both of which have been declared a scientific or unscientific, using logic, everything that has been known empirically as well as on the basis of faith more easily accepted by common sense. Philosophy has the ability to add one's faith in religion, but "if either apply it" will make people doubt his belief in the teachings of the sacred. What according to religious teachings enough to be felt, the philosophies need to be considered, so the feeling for religion is an act of rational and logical.